2014
DOI: 10.1007/s13404-014-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation of gold nanoparticles according to procedures described in the eighteenth century

Abstract: Gold nanoparticles have received much attention in recent years due to their unique size-dependent properties, as they find useful applications in materials science [Mayoral et al. (Nanoscale 2:335-342, 2010) [Sperling et al. (Chem Soc Rev 37:1896-1908, 2008]. The preparation of such nanoparticles benefits from modern chemical knowledge, and a large variety of several procedures have been developed aiming at controlling the size and shape of these metal nanoparticles. Here, we show that two eighteenth-centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…These observations evidence that the gold entities aggregate in the oily phase, through a slow process that takes several days. By comparing these results with those reported for the same two-liquid phase system in which a more concentrated solution of gold was used [13], it can be concluded that a decrease of the gold concentration in aqua regia changes the selectivity of the gold-reduction process toward the By comparing these results with those reported for the same two-liquid phase system in which a more concentrated solution of gold was used [13], it can be concluded that a decrease of the gold concentration in aqua regia changes the selectivity of the gold-reduction process toward the preferential formation of small gold clusters and isolated gold atoms over that of AuNPs, although the latter are still present. These results corroborate the efficiency of this simple two-liquid system to render small gold aggregates and isolated gold atoms.…”
Section: Rosemary Oil Phasementioning
confidence: 86%
See 3 more Smart Citations
“…These observations evidence that the gold entities aggregate in the oily phase, through a slow process that takes several days. By comparing these results with those reported for the same two-liquid phase system in which a more concentrated solution of gold was used [13], it can be concluded that a decrease of the gold concentration in aqua regia changes the selectivity of the gold-reduction process toward the By comparing these results with those reported for the same two-liquid phase system in which a more concentrated solution of gold was used [13], it can be concluded that a decrease of the gold concentration in aqua regia changes the selectivity of the gold-reduction process toward the preferential formation of small gold clusters and isolated gold atoms over that of AuNPs, although the latter are still present. These results corroborate the efficiency of this simple two-liquid system to render small gold aggregates and isolated gold atoms.…”
Section: Rosemary Oil Phasementioning
confidence: 86%
“…Gold clusters were prepared from a two-liquid phase system following a procedure previously described [13][14][15]. A gold lump of 0.3290 g (99.99%, Royston Hertfordshire, UK) was dissolved under gentle stirring in 105.2 g of aqua regia, prepared by mixing (4:1, w/w) concentrated nitric acid (65 wt%, Panreac Química SLU, Castellar del Vallès, Spain) and ammonium chloride (Sigma-Aldrich, >98%, Merck KGaA, Darmstadt, Germany), while heating at 40 • C in a sand bath.…”
Section: Synthesis Of the Gold Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a group of Spanish researchers has been able to reproduce a recipe of Aurum potabile of the eighteenth century and to probe the presence of gold nanoparticles in the solution. 6 A gold cordial was advocated in the seventeenth century for the treatment of ailments caused by a decrease in the vital spirits, such as melancholy, fainting, fevers and falling sickness. Later in the nineteenth century, a mixture of gold chloride and sodium chloride was used to treat syphilis.…”
Section: Gold For Human Well-being: Food Drinks and Medicinementioning
confidence: 99%